2008
DOI: 10.1021/ja8068769
|View full text |Cite
|
Sign up to set email alerts
|

A Facile One-Pot Synthesis of meso-Aryl-Substituted [14]Triphyrin(2.1.1)

Abstract: The synthesis and spectroscopic properties of a series of boron-free meso-aryl-substituted [14]triphyrin(2.1.1) compounds containing either peripheral bicyclo[2.2.2]octadiene (BCOD) (2a−c) or benzene rings (3a−c) (aryl = phenyl a, 4-fluorophenyl b, and 4-methylbenzoatephenyl c) are reported. These compounds represent the first examples of free-base contracted porphyrinoids with 14 π-electron aromatic systems containing only the standard pyrrole and isoindoline moieties of the porphyrins and tetrabenzoporphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
152
4
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 28 publications
6
152
4
2
Order By: Relevance
“…Such an effect is typical for triphyrins(n.1.1). [9,10] The electronic spectrum of 2-H is consistent with the NMR-derived conclusions. An intense Soret-like band is accompanied by a set of Q-bands (Figure 2).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Such an effect is typical for triphyrins(n.1.1). [9,10] The electronic spectrum of 2-H is consistent with the NMR-derived conclusions. An intense Soret-like band is accompanied by a set of Q-bands (Figure 2).…”
supporting
confidence: 83%
“…The behavior resembles that of other triphyrins(n.1.1). [10] To explore the wider applicability of the presented synthetic approach, the calix-triphyrin 4 was synthesized and used here as an appropriate reference point to analyze macrocyclic conjugation. The synthetic approach involves the same strategy as that applied for 2-H, but using 2,5-bis(hydroxydiphenylmethyl)furan (Scheme 1).…”
mentioning
confidence: 99%
“…[1] It is closely related to the abovementioned triaryl tribenzosupporphyrin 3, but carries a (2.1.1) bridge pattern. [1] It is closely related to the abovementioned triaryl tribenzosupporphyrin 3, but carries a (2.1.1) bridge pattern.…”
mentioning
confidence: 94%
“…Porphyrin research keeps up in presenting astonishing results, which is aptly demonstrated by the synthesis of a new free-base (non-metalated) [14]triphyrin(2.1.1) [1] and the very recent formation of tetraazuliporphyrin tetracation. [2] Both compounds owe their stablity to annulation and arylation of the aromatic skeleton with other p-electron-rich rings.…”
mentioning
confidence: 99%
“…In 2008, we reported the first serendipitous synthesis of free-base [14]triphyrinA C H T U N G T R E N N U N G (2.1.1) compounds during a BF 3 ·Et 2 O-catalyzed Lindsey reaction. [7] In contrast to the previously reported subporphyrins which contain a central boron with a bowlshaped conformation, this new triphyrin system may allow new, unique metal complexation behavior in subporphyrin chemistry, together with applications thereof, to be explored for the first time (highlighted by Norbert Jux in Angewandte Chemie [8] ). Although the Lindsey method has been widely used for the synthesis of tetrapyrrole [18]porphyrin over the decades, no triphyrin compounds have ever been reported before.…”
mentioning
confidence: 99%